2011
DOI: 10.1002/j.2334-4822.2011.tb00664.x
|View full text |Cite
|
Sign up to set email alerts
|

21: Faculty Development as a Hazardous Occupation

Abstract: Hazardous" describes events and conditions that produce an undesired, involuntary, career-changing disruption of a developer's professional practice. While faculty development is an immensely valuable asset to an institution that knows how to make use of it, the unique nature of faculty development centers within varied academic institutions brings occupational hazards to those who direct or work in such centers. Our study synthesizes and identifies patterns among over thirty cases furnished by developers, pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Sabagh et al, 2018), minimal research (e.g. Nilson et al, 2011) has investigated the nature of this link, particularly, in the hospitality context. This is particularly prevalent among studies investigating resource-related research topics in collectivist cultures.…”
Section: Relationship Between Workplace Bullying and Well-beingmentioning
confidence: 99%
“…Sabagh et al, 2018), minimal research (e.g. Nilson et al, 2011) has investigated the nature of this link, particularly, in the hospitality context. This is particularly prevalent among studies investigating resource-related research topics in collectivist cultures.…”
Section: Relationship Between Workplace Bullying and Well-beingmentioning
confidence: 99%
“…CTLs have been said to play “‘background roles,’ mostly staying out of the spotlight” (Bartlett, ). The profession has even been referred to as “hazardous” (Nilson et al, ). As much as scholars may wish to retrieve such terms or reveal the positive potential of marginal positions, this kind of rhetoric also implies a place for educational developers that is far from central or secure and not always particularly valued.…”
Section: Gender and Organizational Developmentmentioning
confidence: 99%
“…In short, a significant percentage of participants in a study about marginalization reported not being marginalized at all, especially compared to the relatively few that did report being uninvolved in organizational development. While this is certainly reassuring data, given widespread concerns about the marginal (Chism, ; D'Andrea & Gosling, ; Harland & Staniforth, ) and even “hazardous” (Nilson, Nuhfer, & Mullinix, ) position of educational developers, it is then unclear to what degree these directors’ experiences can shed light on marginalization in our field or what kinds of movements might be required to become more central, given that such movements would hardly be necessary if one is already a “key leader.”…”
Section: Coming In From the Margins: Organizational Development And Tmentioning
confidence: 97%